2011
DOI: 10.1074/jbc.m111.264770
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Human Fumarylacetoacetate Hydrolase Domain-containing Protein 1 (FAHD1) as a Novel Mitochondrial Acylpyruvase

Abstract: Background: Human FAHD1 is a member of the FAH enzyme superfamily with unknown enzymatic activity.Results: FAHD1 exhibits acylpyruvase activity, demonstrated by the hydrolysis of acetylpyruvate and fumarylpyruvate in vitro.Conclusion: We identified mammalian FAHD1 as a novel mitochondrial enzyme with acylpyruvate hydrolase activity.Significance: We here identify a so far undescribed enzyme activity in human mitochondria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
42
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 16 publications
2
42
1
Order By: Relevance
“…Interestingly, the enzyme kinetics of FAHD1 closely resemble some of the values reported for an unidentified mammalian ODx in earlier years [4,3]. The mutation of key residues located within the catalytic domain, including a catalytic loop, resulted in abrogated or reduced enzymatic activity.As already observed in an earlier study [8], FAHD1 is located in mitochondria, showing highest expression in kidney and liver. Oxaloacetate levels in the kidneys and livers of FAHD1-/-mice were significantly increased in comparison to their wildtype littermates, thereby providing evidence for the in vivo relevance of FAHD1's ODx activity.…”
supporting
confidence: 59%
See 1 more Smart Citation
“…Interestingly, the enzyme kinetics of FAHD1 closely resemble some of the values reported for an unidentified mammalian ODx in earlier years [4,3]. The mutation of key residues located within the catalytic domain, including a catalytic loop, resulted in abrogated or reduced enzymatic activity.As already observed in an earlier study [8], FAHD1 is located in mitochondria, showing highest expression in kidney and liver. Oxaloacetate levels in the kidneys and livers of FAHD1-/-mice were significantly increased in comparison to their wildtype littermates, thereby providing evidence for the in vivo relevance of FAHD1's ODx activity.…”
supporting
confidence: 59%
“…Classification of their function has proven difficult due to the aforementioned spectrum of FAH fold activities. In a first study, the comparison of FAHD1's primary sequence with prokaryotic members of the FAH family led to the observation that FAHD1 exhibits acylpyruvate hydrolase activity [8].…”
mentioning
confidence: 99%
“…Expression and Evidence for in Vivo Activity in Mice-Previous studies, using a polyclonal antiserum raised against recombinant FAHD1 protein, indicated a widespread expression pattern for FAHD1 in many mouse tissues, based on two distinct bands revealed by Western blot (10). In view of the specific ODx activity for FAHD1 revealed here, the expression pattern of FAHD1 was reinvestigated by improved immunological reagents.…”
Section: Journal Of Biological Chemistry 6759mentioning
confidence: 99%
“…Bacterial Recombinant Expression and Purification of FAHD1-N-terminally His-and S-tagged versions of human wild-type FAHD1 and three mutants (H30A, E33A, and D102A/R106A) were recombinantly expressed in E. coli and purified as reported previously (10).…”
Section: Structural Investigation Of the Fah Domain Active Sites-mentioning
confidence: 99%
See 1 more Smart Citation